Saturday

April 19, 2014

April 19, 2014

Posted by **math** on Thursday, January 13, 2011 at 8:47am.

- algebra -
**Reiny**, Thursday, January 13, 2011 at 10:28amdid you notice that

x^2 - 7x + 12 = (x-4)(x-3) which happen to be denominators of the first 2 terms?

So the LCD is (x-4)(x-3)

Multiply each term by that LCD to get

2x(x-3) + 4(x-4) = 8

2x^2 + 4x - 30 = 0

x^2 + 2x - 15 = 0

(x+5)(x-3) = 0

x = -5 or x = 3

BUT x=3 would make the expression undefined,

so

x = -5

**Related Questions**

Algebra - Solve by using the quadratic formula x^2=-7x+12 First, put all the ...

College Algebra - I need help factoring a problem and cant seem to get it right...

math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Algebra 1 - Add (5x^2 - 2x + 9) + (2x^2 - 4). My answer: 7x^4 - 2x + 5 or 7x^2...

Help With Math - Using the quadratic formula to solve equations. -12^2 + 12 x-9...

Calculus 2 correction - I just wanted to see if my answer if correct the ...

Math - Can someone please check my answers below for accurateness? The ...